Fibroblasts in Scar Formation: Biology and Clinical Translation. (12th May 2022) - Qian, Huan; Shan, Yihan; Gong, Ruicheng; Lin, Danfeng; Zhang, Mengwen; Wang, Chen; Wang, Lu
Abstract : Scarring, which develops due to fibroblast activation and excessive extracellular matrix deposition, can cause physical, psychological, and cosmetic problems. Fibroblasts are the main type of connective tissue cells and play important roles in wound healing. However, the underlying mechanisms of fibroblast in reaching scarless wound healing require more exploration. Herein, we systematically reviewed how fibroblasts behave in response to skin injuries, as well as their functions in regeneration and scar formation. Several biocompatible materials, including hydrogels and nanoparticles, were also suggested. Moreover, factors that concern transformation from fibroblasts into cancer-associated fibroblasts are mentioned due to a tight association between scar formation and primary skin cancers. These findings will help us better understand skin fibrotic pathogenesis, as well as provide potential targets for scarless wound healing therapies.